Acute endocrinology from cause to consequence - Berghe, Greet Van den. (Contemporary endocrinology, 2008)
The integration of endocrinology in critical care medicine has led to new experimental and clinical data on the complex endocrine and metabolic derangements accompanying non-endocrine severe illnesses. The joining of these two disciplines has generated important novel insights with significant clinical implications. Acute Endocrinology: From Cause to Consequence compiles these new findings into an important and highly relevant new resource. Part one deals with the classical life-threatening illnesses caused by primary endocrine diseases such as thyrotoxicosis, hypothyroidism, acute adrenal crisis, acute calcium disorders, pheochromocytoma, severe hyper- and hypoglycemia. Part two looks at endocrinology from the ICU side, starting with a general overview of the dynamic neuroendocrine and metabolic stress responses in the condition of intensive care-dependent, non-endocrine critical illness. Acute Endocrinology: From Cause to Consequence provides a unique and up-to-date overview of the joining of these two disciplines and seeks to stimulate further interdisciplinary research in this important and exciting field. Endocrine diseases causing potentially life-threatening emergencies -- Thyrotoxicosis -- Myxedema coma -- Acute adrenal crisis -- Acute calcium disorders -- Phaeochromocytoma and other diseases of the sympathetic nervous system -- Hyperglycemic crises: Diabetic Ketoacidosis (DKA) and Hyperglycemic Hyperosmolar State (HHS) -- Hypoglycemia: an endocrine emergency -- Endocrine disturbances caused by non-endocrine critical illnesses -- The dynamic neuroendocrine response to critical illness -- Changes within the GH/IGF-I/IGFBP axis in critical illness -- Changes within the thyroid axis during the course of critical illness -- The adrenal response to critical illness -- Catecholamines and vasopressin during critical illness -- The diabetes of injury: novel insights and clinical implications -- Disorders of body water homeostasis.